Expansion of Agricultural Zakat Revenue in Malaysia on the Basis of the Current Maslahah - Ab Rahman, Muhamad Firdaus; Abdullah Thaidi, Hussein `Azeemi; Baharuddin, Ahmad Syukran; Ab Rahman, Azman; Ab Rahim, Siti Farahiyah (Al-Jami'ah Research Centre, 2019)
The reality concerning the agricultural zakat in Malaysia only impose the zakah on the paddy crops based solely on the opinion of Imam Shafi`i rather than an opinion of other scholars. This paper aims to critically examine the agricultural zakat in Islam based on Malaysian context and analyse the transformation of expanding the agricultural zakat based on the objective of Shariah. A qualitative methodology was employed to analyse the data through inductive, deductive, comparative and field research. As for the field research, the study has conducted semi-structured interviews with the Zakat Corporation, Islamic Religious Council and Mufti`s Department in the selected states in Malaysia, namely: Selangor, Penang, Terengganu and Sarawak. The finding demonstrated that the revenue of the agricultural-based zakat could be expanded according to the view held by Imam Hanafi and its benefit to the current agricultural economy. Thus, this paper proposes that every State’s Zakat Corporations and Islamic Religious Councils in Malaysia should reassess the existing ruling and legal framework of agricultural zakat in order to realize its revenue expansion as an effective solution for the current zakat collection. [Realitas zakat pertanian di Malaysia lebih mengutamakan qaul Imam Shafi`i dibandingkan dengan qaul-qaul mazhab lain. Pengelolaan zakat di Malaysia hanya dikenakan pada zakat pertanian dan terbatas kepada makanan pokok, yaitu padi. Artikel ini bertujuan untuk menganalisis secara kritis zakat pertanian dalam konteks Malaysia serta mengkaji transformasi isu meluaskan zakat pertanian kepada tanaman selain padi berdasarkan maqasid syari’ah. Kajian ini menggunakan metode kualitatif, dimana analisis data menggunakan kaedah induktif, deskriptif, dan komparatif. Kajian lapangan juga dilakukan dalam bentuk wawancara dengan Jabatan Mufti Negeri dan Baitulmal Negeri di Malaysia; seperti Selangor, Pulau Pinang, Perlis, Terengganu dan Sarawak. Hasil kajian menunjukkan bahwa hasil zakat pertanian dapat diperluas berdasarkan pendapat Imam Abu Hanifah yang lebih sesuai dengan maslahah ekonomi pertanian saat ini di Malaysia. Dengan demikian, studi ini mengusulkan bahwa lembaga zakat setiap negeri dan Dewan Agama Islam di Malaysia harus mengkaji kembali kerangka hukum zakat pertanian yang ada dalam rangka merealisasikan ekspansi penghasilannya sebagai solusi efektif untuk pengumpulan zakat saat ini.]